A beachcomber's bonanza, or just another Micraster?. (17th August 2022) - Donovan, Stephen K.
Abstract : The beach is where the ancient, in the shape of diverse erratics, meets the present in the shape of corrosion, encrusting shells and invertebrate borings. Many of us have favourite beach walks, repeated whenever possible, and educating us in the common and rare clasts that might be encountered in such an ever‐changing environment. After over 12 years of patrolling the coast of north Norfolk, in eastern England, I found a common Chalk echinoid—so why am I excited?